2011
DOI: 10.1111/j.1741-2358.2011.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete denture wearing and fractures among edentulous patients treated in university clinics

Abstract: Complete denture wearing and fractures among edentulous patients treated in university clinicsObjective: The prevalence of wearing and fracture of complete dentures was evaluated among edentulous patients treated in two dental schools in Brazil. Background: Acceptance and wearing of complete dentures are related to adaptive behaviour of edentulous patients. However, one reason that could interfere with the wearing dentures is their potential to fracture, which is still a common complication in denture rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
(69 reference statements)
0
34
0
1
Order By: Relevance
“…The denture fracture may result from flexural forces due to, for example, the improper fabrication, poor fit or lack of balanced occlusion [40]. Moreover, most PMMA partial or complete dentures are removable; thus, their resistance to shock-induced fractures, represented by impact strength, is no less important due to the possibility of their falling or being damaged during the action of violent forces caused by other events [41]. Between 39.5% and 56% of fractures occur as a result of the fall of dentures [41,42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The denture fracture may result from flexural forces due to, for example, the improper fabrication, poor fit or lack of balanced occlusion [40]. Moreover, most PMMA partial or complete dentures are removable; thus, their resistance to shock-induced fractures, represented by impact strength, is no less important due to the possibility of their falling or being damaged during the action of violent forces caused by other events [41]. Between 39.5% and 56% of fractures occur as a result of the fall of dentures [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most PMMA partial or complete dentures are removable; thus, their resistance to shock-induced fractures, represented by impact strength, is no less important due to the possibility of their falling or being damaged during the action of violent forces caused by other events [41]. Between 39.5% and 56% of fractures occur as a result of the fall of dentures [41,42]. Other material properties that affect the durability of PMMA dentures are their hardness and wear resistance which determine the surface conditions of prosthetic materials [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…They include limited resistance to mechanical damage related to low elasticity and changes in volume and shape during the production and use of dentures made thereof [1,2]. Searching for methods to increase acrylic strength showed that it's caused by a high percentage of cracks and breaks of RPD [3][4][5]. Statistic surveys show the necessity to repair 30-50 % of dentures used by patients [6].…”
Section: Ocena Wytrzymałości Mechanicznej Poli(metakrylanu Metylu) Wzmentioning
confidence: 99%
“…The determined parameters allowed the specification of PMMA ability to resist deforming occlusion forces, similarly as in patients using the upper denture during chewing [1,[3][4][5].…”
Section: T a B L E 1 Comparison Of Composition And Parameters Of Thementioning
confidence: 99%
“…The cracking and fracturing of denture bases is still an unresolved clinical complication in dental practice. It is the primary cause of the failure of the removable prosthesis [3]. Denture base fracture is primarily attributed to poor mechanical properties like low impact strength and reduced fatigue resistance [4].…”
Section: Introductionmentioning
confidence: 99%